Health-related quality of life is a significant prognostic factor for recurrence and overall survival in patients with colon cancer - Catarina Tiselius; Fanny Johansen; Andreas Rosenblad; Kenneth Smedh (BMC Cancer)
Abstract Background Health-related quality of life (HRQoL) is associated with survival in patients with cancer; however, there are few studies on the risk of cancer recurrence. We investigated whether HRQoL can predict disease-free and overall survival (DFS/OS) in patients with non-metastatic colon cancer. Methods This population-based prospective study investigated patients diagnosed with colon cancer between 2012 and 2016. The 30-item European Organisation for Research and Treatment of Cancer Core Quality of Life Questionnaire (EORTC QLQ-C30) was used to measure HRQoL at diagnosis. Cox proportional hazard regression analyses were used to analyse the association between QLQ-C30 scores and DFS/OS. Results Of the 323 patients with non-metastatic colorectal cancer, n = 41 (12.7%) were diagnosed with recurrence during mean (standard deviation) DFS and OS follow-up times of 5.9 (2.9) and 6.2 (2.7) years, respectively. Cox regression analysis of HRQoL, adjusted for important clinical and demographic variables, showed that a higher global health status was significantly associated with an improved DFS (hazard ratio [HR] 0.86 per 10 points; 95% confidence interval [CI] 0.79–0.94; P < 0.001) as well as OS (HR 0.88 per 10 points; 99% CI 0.80–0.96; P = 0.003). Conclusions These results demonstrate that HRQoL can predict both DFS and OS in patients with non-metastatic colon cancer. HRQoL should be considered an additional tool in non-metastatic cancer for assessing patients at risk of metastatic disease. Trial registration ClinicalTrials.gov (NCT 03910894).